2022
DOI: 10.1088/1361-6382/ac4b03
|View full text |Cite
|
Sign up to set email alerts
|

On the duality of Schwarzschild–de Sitter spacetime and moving mirror

Abstract: The Schwarzschild-de Sitter (SdS) metric is the simplest spacetime solution in general relativity with both a black hole event horizon and a cosmological event horizon. Since the Schwarzschild metric is the most simple solution of Einstein's equations with spherical symmetry and the de Sitter metric is the most simple solution of Einstein's equations with a positive cosmological constant, the combination in the SdS metric defines an appropriate background geometry for semi-classical investigation of Hawking ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 77 publications
(107 reference statements)
1
7
0
Order By: Relevance
“…As we shall see, the non-equilibrium transition between thermal states is full of new information, as highlighted by the confluent hypergeometric function in equation (21). Likewise, spectral variations on the characteristic transition between thermal states will also be present between horizons, as illustrated in the following section.…”
Section: Transition Connecting Cw Accelerationsmentioning
confidence: 83%
See 2 more Smart Citations
“…As we shall see, the non-equilibrium transition between thermal states is full of new information, as highlighted by the confluent hypergeometric function in equation (21). Likewise, spectral variations on the characteristic transition between thermal states will also be present between horizons, as illustrated in the following section.…”
Section: Transition Connecting Cw Accelerationsmentioning
confidence: 83%
“…Finally, we can extend the solution of ABC with Schwarzschild-de Sitter spacetime as given in [21] (which approximates by neglecting the third term) to include the full solution with all three terms present. The approximated Bogoliubov coefficient considering only two terms involves the confluent hypergeometric function of one variable.…”
Section: Between Two Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this, we can explore the relation between mirrors, and hence spacetimes, with identical flux, such as thermal emission from de Sitter space [26,27] and the Carlitz-Willey (CW) [28] mirror, investigate cases with merely asymptotically identical flux, and probe the zero energy, but nonzero particle, production of uniformly accelerating motion, whose asymptotic dynamics corresponds to extremal black holes [6,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerating mirrors can be considered as an analogue of the dynamical Casimir effect in (1+1) dimensions [34,35], a prototype for black hole evaporation [36][37][38][39][40]. It has been observed that there is a strong connection between accelerating mirrors and black hole physics [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%